Contemporary Australian Literature : A World Not Yet Dead - Birns, Nicholas (Sydney Sydney University Press)
Australia has been seen as a land of both punishment and refuge. Australian literature has explored these controlling alternatives, and vividly rendered the landscape on which they transpire. Twentieth-century writers left Australia to see the world; now Australia's distance no longer provides sanctuary. But today the global perspective has arrived with a vengeance. In Contemporary Australian Literature: A World Not Yet Dead, Nicholas Birns tells the story of how novelists, poets and critics, from Patrick White to Hannah Kent, from Alexis Wright to Christos Tsiolkas, responded to this condition. With rancour, concern and idealism, modern Australian literature conveys a tragic sense of the past yet an abiding vision of the way forward. Birns paints a vivid picture of a rich Australian literary voice - one not lost to the churning of global markets, but in fact given new life by it.
English
Keywords: Literature: history & criticism; Literature; Australian literature; literary studies; literary criticism; Australian literary criticism; literature and neoliberalism; Australia; Australian literature; Neoliberalism